Mifepristone for cervical ripening and induction of labour - G., Lata; N., Rana; R., Mittal; S., Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The study was aimed to evaluate the efficacy of Mifepristone for induction of labour and in improving the Bishop score at term. The study also aimed to assess induction delivery interval and maternal and fetal outcomes with Mifepristone. Methods: The study was carried out on 200 pregnant females with 2 study groups of 100 each. Group A females received tablet Mifepristone 400mg and Group B females received placebo. Results: Time interval between induction to onset of labour was 28 hours 54 min and 42 hours 18 min respectively in cases and control group. Mean induction delivery interval was 35 hours 38 min and 49 hours 52 minutes respectively in cases and control group. LSCS rate was less with Mifepristone group. Conclusions: This study showed that treatment with Mifepristone is a simple and effective method of inducing labour in women with term pregnancy with unripe cervix. The use of Mifepristone provides an interesting new alternative to classic uterotonic agents when induction is necessary. The potential advantage of Mifepristone over PGs or oxytocin requires further evaluation in scarred uterus.